Characteristics and main controlling factors of Ordovician deep subsalt reservoir in central and eastern Ordos Basin, China - Ling Fu; Jianzhong Li; Wanglin Xu; Wei Guo; Ningxi Li; Yueqiao Zhang; Wei Song; Yuanshi Sun (Journal of Natural Gas Geoscience, 2021)
In recent years, the subsalt dolomite reservoirs in the Ordovician strata of the Ordos Basin have indicated good exploration results and are expected to have a high hydrocarbon potential. This study targets the Ma 3 and Ma 4 reservoirs below the salt rock of the Ordovician in the central and eastern Ordos Basin. It investigates the reservoir characteristics and main controlling factors of high-potential reservoirs by combining core observations, cast slabs, scanning electron microscopy, physical property analysis, and mercury injection data. The results show that the Ma 3 reservoir is dominated by gypsum-bearing dolomite deposited in evaporation environments, whereas the Ma 4 reservoir is dominated by calcite dolomite under a transgressive environment. The types of Ma 4 reservoir space mainly include dissolved pores (dissolved holes), intra-crystalline pores, intra-crystalline dissolved pores, and microcracks. The types of Ma 3 reservoir space mainly include microcracks, gypsum mould pore, dissolved pores (dissolved holes), and intergranular pores. The pore structures of reservoirs are complex. The capillary pressure curves can be divided into four types: dissolved pore type, intra-crystalline (dissolved) pore type, microcrack type, and micro-porous type. Based on available information, the average porosity values of the Ma 3 and Ma 4 reservoirs are 2.1% and 2.3%, respectively, and the average permeability values are 0.19 × 10−3μm2 and 0.22 × 10−3μm2, respectively. The Central paleo-uplift, the Wushenqi secondary paleo-uplift, and the Shenmu low uplift controlled the sedimentary facies and favorable lithofacies distributions. Sedimentary microfacies control rock fabric, and the rock fabric affects the physical properties of the reservoirs. The limestone and dolomite reservoirs with gypsum and sand cutting texture have relatively good physical properties. Diagenesis is also a key factor in the development of sub-salt reservoirs. Intra-crystalline pores are mainly formed under various dolomization mechanisms. The surficial and buried diagenetic environments facilitate the formation of a large number of secondary pores, such as dissolved pores (dissolved holes), intra-crystalline dissolved pores, and gypsum mould pores. In addition, the Yanshan tectonic activity played a vital role in the development of reservoir microcracks. The microcracks can significantly improve reservoir physical properties. It is favored that the tectonic setting, rock fabric, diagenetic, and microcrack alterations collectively determine the sub-salt reservoirs' storage capacity and are the main controlling factors for forming high-quality reservoirs.